Strategi pengelolaan sampah rumah tangga: Tinjauan terhadap upaya pemberdayaan, edukasi, dan inovasi lingkungan - Panggalih, Stella Ega (Maliki Interdisciplinary Journal, 2025)
Household waste management is an environmental issue that continues to grow in line with increasing levels of public consumption. Improper waste management can have negative impacts on health, the environment, and the overall quality of life. This study aims to identify and analyze various household waste management strategies that have been implemented in different regions, with an emphasis on community empowerment, environmental education, and the application of innovative approaches. These strategies include a wide range of initiatives such as community-based waste management, the utilization of organic and inorganic waste, and the development of environmentally friendly technologies. This review is expected to contribute to a more comprehensive understanding of sustainable waste management practices and serve as a foundation for policy development and program implementation at both local and national levels.